Prediksi Penyediaan Stok Barang Pada Toko Mintxchoco Merchandise Surabaya Menggunakan Algoritma Apriori - Anggi Rizki Septiani; Alfarizi Kurniawan Lesmana; Aryo Nugroho (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2021)
The number of sales transactions that occur every day makes the sales transaction data increase. Sales transaction data is only used as an archive for a store. Due to the large number of customer requests for goods, there is a shortage of goods. Shortage or stock of goods in a store/company will have a very bad impact on the success and sales of buying and selling transactions. To prevent this, a system is needed that can help to find out early about the availability of goods in the store. The method used in this research is the association rule method using a priori algorithm. The a priori algorithm is a data mining technique to find combinations of items in the database, the results of the research conducted, the a priori algorithm can make it easier to find patterns of combinations of items in the dataset. The information obtained can help decision makers to determine the priority of stock inventory.